ON THE INFLUENCE OF IDEOLOGICAL AND GEOPOLITICAL DOCTRINES OF THE WEST ON THE FORMATION OF A MODERN SERBIAN STATE - Šuljagic, Sanja (National interest, 2025)
The subject of research in this monographic study is the inﬂuence of ideological and geopolitical doctrines of the West on the formation of the modern Serbian state in the 19th century. The research aims to understand European states’ prevailing inﬂuence on a geopolitical constellation in the Balkan Peninsula in the abovementioned period. Within this monographic study, analytic-synthetic and comparative methods are implemented in the presentation of: the formation of Western political philosophy; the change of traditional Serbian identity before and during the formation of the modern Serbian state; and the prevention of the revival of the concept of pre-Osman Christian Orthodox states. Conclusion of the research in this monographic study is that one of frst preconditions for the formation of modern Serbian and other Balkan states under direct or indirect control of European Welf-Hanover dynasty and its dynasty branches was a centuries long premodern colonial domination of representatives of Venetian and Genoese slavery and merchant companies, whose political philosophy directly and indirectly inﬂuenced development of later European powerful navies and also later political processes in the Balkan peninsula. Western geopolitical interests were clashing with the geostrategy of the Russian Empire in the Balkans. Tzarist Russia was, in a geopolitical sense, substantial for the formation of the Balkan Christian states, the Serbian one included, but modern Western political philosophy prevailed in the formation of the ideological inclination of the Balkan peoples.
Keywords: West; modern Serbia; identity; ideology; doctrine; geopolitics; modernity; colonialism; Christian Orthodoxy; state